PENGARUH GAYA KEPEMIMPINAN, LINGKUNGAN KERJA, SIFAT PEKERJAAN DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA PEGAWAI NEGERI SIPIL PADA DINAS KOPERASI USAHA MIKRO KECIL DAN MENENGAH KABUPATEN BELU - Desiderata, Yesus (PRODI EKONOMI PEMBANGUNAN, STIE MUHAMMADIYAH TANJUNG REDEB, 2018)
Problem found and interested to be studied is the low of work satisfaction from the most of civil cervant on duty little and intermediate micro effort corporation Belu regency. It?s predictable influenced by leaderships style, work environment, job character, and civil cervant?s work motivation.To analyze the problem found, the writer chose 20 civil cervants as the sample by using cold-drawn sampling. The data gathered from both primary and secondary sources then it?s analyzed by descriptive statistic and inferencial with SPSS (Statistical Package For Social Science) software support release 20. The result of research shows that the value of hypothesis probality test partially and simultaneously smaller than alpha 0, 05 so it shows that leaderships style, work environment, job character, and civil cervant?s work motivation partially and simultaneously is significance influenced to work satisfaction of civil cervant on duty little and intermediate micro effort corporation Belu regency. The result of analyzis standardized bifilar linear regression shows that work environment as the bigest factor that influenced to civil cervants? work satisfaction with ?2 = 0,563 coefficient regression while work motivation as the smallest factor that influenced to civil cervants? work satisfaction with ?4 = 0,173 coefficient regression. Simultaneously, leaderships style, work environment, job character and work motivation has influence 74, 80 % to civil cervants? work satisfaction while 25, 20 % is influenced by another factors which didn?t include in model used or which isn?t be studied because of constant assumed.